Quantitative analysis of free sphingoid bases in the brain and spinal cord tissues by high-performance liquid chromatography with a fluorescence detection - Kwon, OS; Newport, GD; Slikker, W (ELSEVIER SCIENCE BV, 1998)
The o-phthaldialdehyde precolumn derivatives of psychosine, sphinganine and sphingosine extracted from brain and spinal cord tissues were determined by high-performance liquid chromatography-fluorescence detection. This method was developed with the purpose of detecting an endogenous amount of psychosine, sphingosine and sphinganine using small aliquots of brain tissues and spinal cord in rats. These sphingolipid bases were extracted in various ratios of chloroform-methanol and several pH values. Recovery of the method is about 81% in 12 ng/tube (final volume, 320 mu l), 90-95% in 45 ng/tube of sphingosine and sphinganine within 2-12% relative standard deviation. Detection limits of these sphingoid bases were about 0.05 pmol/mg brain tissue. In the forebrain, brainstem and spinal cord of rats at three different ages of postnatal days (PND) 1, PND 13 and 6 months old, the endogenous concentrations of psychosine, sphingosine and sphinganine were determined. From these results, this method is suitable for the determination of sphingoid bases in small aliquot of brain and spinal cord tissues. (C) 1998 Elsevier Science B.V. All rights reserved.